Impact of climate change on the suitability of major crops in the eastern Kansas River basin - Sen, Rintu (Kansas State University, 2023)
Climate change will have a considerable impact on agricultural production and its associated processes all around the world, along with an increase in the frequency and intensity of extreme events (like floods and droughts), introducing uncertainty and vulnerability into the agricultural systems. Rainfed crop production system is especially more vulnerable to these extreme effects of climate change. Though the focus area of this study, Eastern Kansas River Basin (EKSRB), lies in the humid northeastern part of Kansas; and is also expected to experience increasing aridity. Keeping this in mind, this study was undertaken to assess the suitability of growing primary cash crops in the region under a changing climate. The crop simulation model, Decision Support System for Agrotechnology Transfer (DSSAT), was used to simulate maize and soybean yields under baseline (1990-2019) and future (2006-2099) climate scenarios. CERES-Maize and CROPGRO-Soybean models in DSSAT were calibrated and validated using observed yield data from USDA NASS with long-term historical weather data, soils data from gSSURGO to account for spatial variability of soils in the study area. The eighteen downscaled Global Climate Models (GCMs) under two Representative Concentration Pathways (RCP4.5 and RCP8.5) were used for projecting future yields. Finally, yield gap percentage (YG[subscript percentage]) was used to determine future crop-suitable growing areas in the EKSRB. The highest yield loss observed for maize and soybean was 45% and 30% under RCP8.5 at the end of the century. The increasing yield gap trend for both crops under both RCPs points towards the reduction of the suitability of growing maize and soybean in the EKSRB under future climate change scenarios. The results showed that soybean could be a more robust crop under future climate change conditions.
Keywords: Climate change; GCM; DSSAT; Rainfed; Maize and soybean; Suitability